Normatywne modele sankcji nieważności bezwzględnej a nieistniejąca czynność prawna: [Normative models of sanctions of absolute nullity and non-existent juridical act] (Studia Prawnicze / The Legal Studies, 2010)
Zagadnienie negotium non existens stanowi refleks znacznie szerszego problemu, jakim jest oddziaływanie w danym systemie prawa przyjętego modelu sankcji nieważności bezwzględnej, tj. ogólnie ujmując, instrumentu prawnego powodującego, że w wyniku dokonania czynności prawnej (złożenia oświadczenia woli)nie doszło do wywołania żadnych zamierzonych skutków prawnych.Z perspektywy konstruowania instrumentów powodujących z mocy prawa, że czynność prawna nie wywoła żadnych zamierzonych skutków prawnych,a już powstałe skutki prawne są nieważne (tj. sankcji nieważności bezwzględnej),można sformułować pewną uwagę ogólną, że poglądy na temat negotium non existens (jako szczególnej odmiany wadliwej czynności prawnej), są z reguły reakcją na pewne niedoskonałości normatywnego modelu sankcji nieważności bezwzględnej. Szczególnie w aspekcie pewnych formalnych ograniczeń możliwości stosowania sankcji nieważności bezwzględnej. Przypisanie czynności prawnej cechy „nieistnienia” – odmiennego od nieważności – może być także pewnym remedium naproblem z wykładnią norm sankcjonowanych nieważnością bezwzględną,w szczególności brakiem możliwości zastosowania sankcji nieważności bezwzględnej, pomimo np. sprzeczności z prawem stanowionym danej czynności prawnej. The article discusses the concept of the so-called negotium non existens (nonexistent juridical act, especially contract) from the point of view of various normative models of absolute nullity i.e. this type of nullity which makes an juridical act automatically legally ineffective (in common law an equivalent of void contracts). The main objective of the article is to justify a thesis that in the light of the general model features of sanctions of absolute nullity and invalidity features, the rejection of this structure should be postulated. The basic argument is a contradiction between the concept of invalidity and the difficulties to specify criteria of differentiating between the sanction of non-existence and the sanction of absolute nullity. Both void and non-existent juridical acts are treated by the law as if they had never existed or happened and can not be enforced. The scope of the article covers Polish law and also main occurrences of nonexistent juridical acts presented in some legal systems of ius civile and the common law tradition. There is no consistent approach as to where defects make contract non-existent or “only” void – e.g. in the contracting process. Special attention was paid to the French legal viewpoint, where the concept of non-existent contracts has gained a particularly strong position and was widely accepted as a result of, inter alia, the operation of the pas de nullité sans texte principle. According to the reform in the realm of the law of obligation (the socalled Catala’s draft) the drafters proposed that the concept of non-existent contracts (juridical acts) should be rejected by law. The article also takes into account the standpoints expressed in the so-called private projects of contract law unification with regard to the concept of non-existent juridical acts, where only the Gandolfi draft contract code has codified this concept as an alternative to void contracts. The distinguishing of the category of the so-called non-existent juridical act refers to a reflection of a much wider problem, namely the impact of the adopted model of the sanction of absolute nullity upon a given system of private law. In this context, the article presents one of the basic aspects of the negotium non existens concept, which is an influence of certain imperfections of the normative model of nullity upon the distinguishing of such invalid juridical acts. The concept of the so-called “non-existent” juridical act may even be an object of codification, as a separate remedy to invalidate juridical acts. Due to significant variations in understanding the notion of nullity in the area of private law, especially contract law, the article also discusses basic features of nullity as a sanction – i.e. a sanctioning norm which means that a juridical act does not produce any intended legal effects. This article held that a distinction should be made between invalidity and the sanction of nullity. For invalidity is presented as a final effect of application of different sanctions of defective juridical acts, including a consequence of a sanction of absolute nullity. Meanwhile, the article defines absolute nullity as one of the sanctions of invalidity which, as a principle, makes a juridical act null and void from the beginning and no intervention of a court is needed. At the same time, it is not possible to talk about a uniform model of formal features of this sanction, which is confirmed by a comparative review of different kinds of nullity. Depending on a given norm, a model of absolute nullity (or analogous type of nullity) may be subject to modifications. With reference to such modifications of statutory (normative) models of sanctions of absolute nullity, a question may arise with finding legal grounds to avoid defective juridical acts. In such cases, the concept of negotium non existens is applied to justify the legal grounds on which a juridical act is void from the beginning, if, due to certain reasons, for instance a limitation period, it is not possible to apply this sanction of nullity.